1999
DOI: 10.2337/diabetes.48.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-selective expression of the five somatostatin receptors (hSSTR1-5) in human pancreatic islet cells: a quantitative double-label immunohistochemical analysis.

Abstract: We have developed a panel of rabbit polyclonal antipeptide antibodies against the five human somatostatin receptor subtypes (hSSTR1-5) and used them to analyze the pattern of expression of hSSTR1-5 in normal human islet cells by quantitative double-label confocal fluorescence immunocytochemistry. All five hSSTR subtypes were variably expressed in islets. The number of SSTR immunopositive cells showed a rank order of SSTR1 > SSTR5 > SSTR2 > SSTR3 > SSTR4. SSTR1 was strongly colocalized with insulin in all beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
187
2
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(199 citation statements)
references
References 0 publications
9
187
2
1
Order By: Relevance
“…Astrocytes have been implicated in the delivery of glucose and lactate to neurons (19) and are known to play an important role in the uptake and recycling of neuronally released glutamate (20). In this respect it is of interest that glutamine synthetase in human cerebral cortical astrocytes is localized in a manner that closely resembles the perisynaptic astrocytic localization of NPC1 in this study (16).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Astrocytes have been implicated in the delivery of glucose and lactate to neurons (19) and are known to play an important role in the uptake and recycling of neuronally released glutamate (20). In this respect it is of interest that glutamine synthetase in human cerebral cortical astrocytes is localized in a manner that closely resembles the perisynaptic astrocytic localization of NPC1 in this study (16).…”
Section: Discussionmentioning
confidence: 67%
“…Confocal Microscopy. Human fetal astrocytes were grown on glass coverslips, fixed in 4% paraformaldehyde, and processed for double-label fluorescence colocalization of NPC1 and LAMP2 (a marker for late endosomes and lysosomes) (8,15) by using NPC1-C primary antibody (1:400) with rhodamine-conjugated anti-rabbit IgG secondary antibody (1:100) or mouse monoclonal anti-human LAMP2 IgG primary antibody (1:250) and fluorescein-conjugated goat anti-mouse IgG (1:100) (8,13,16). The fluorescent images were visualized on a Zeiss LSM410 confocal microscope equipped with an Argon͞Krypton laser.…”
Section: Animalsmentioning
confidence: 99%
“…TaqMan analysis revealed that levels of GPR40 mRNA expression in pancreatic islets were 20-fold higher than those in the pancreas in the same individuals. Notably, the mRNA level of the GPR40 gene in isolated islets was comparable to those of genes encoding GLP1R, ABCC8 (SUR1) and SSTRs, all of which are abundantly expressed in human pancreatic islets [13][14][15][16].…”
Section: Discussionmentioning
confidence: 92%
“…We measured mRNA expression of the GPR40 gene as well as genes encoding sulfonylurea receptor 1 (ABCC8, previously known as SUR1) [13], glucagon-like peptide 1 receptor (GLP1R) [14,15] and somatostatin receptor (SSTR) 3 and 5 [16] using the following method. Total RNA was extracted using the Qiagen RNeasy Mini Kit (Qiagen, Hilden, Germany) [17].…”
Section: Participants Tissue Sampling and Pancreatic Islet Preparationmentioning
confidence: 99%
“…The aim of the study was to validate the use of 68 Ga-DOTANOC as effective and widely available alternative to 18 F-DOPA in CHI. Although, somatostatin analogues (e.g., 68 Ga-DOTANOC) with high affinity to the somatostatin receptor (SSTR) subtypes 2, 3, and 5, should be taken up by the endocrine cells of the islets of Langerhans expressing all SSTR subtypes [11], only little information is available in the literature regarding the usefulness of radiolabelled somatostatin analogues in CHI [12,13]. Indeed, this is the first and well-conducted comparison of such radiotracers in CHI.…”
mentioning
confidence: 99%